A multicenter phase I study of preoperative chemoradiotherapy with S-1 and irinotecan for locally advanced lower rectal cancer (SAMRAI-1). Issue 2 (August 2016) - Sato, Takeo; Hayakawa, Kazushige; Tomita, Naohiro; Noda, Masafumi; Kamikonya, Norihiko; Watanabe, Toshiaki; Kato, Daiki; Sakai, Yoshiharu; Hiraoka, Masahiro; Shimada, Mitsuo; Ikushima, Hitoshi; Baba, Hideo; et al.
Abstract: Background and purpose: Preoperative 5-fluorouracil-based chemoradiotherapy is a standard treatment for locally advanced lower rectal cancer (LALRC). We performed a phase I study to develop a new regimen combining irinotecan and S-1. Materials and methods: Patients with LALRC (T3-4, N0-2) were studied. The radiation dose was 45 Gy in 25 fractions. S-1 (80 mg/m 2 /day) was administered on days 1–5, 8–12, 22–26, and 29–33. Irinotecan was administered on days 1, 8, 22, and 29. The dose of irinotecan was initially 60 mg/m 2 (level 1). Surgery was performed 6–10 weeks after the chemoradiotherapy. Results: Twenty patients were enrolled, of whom 18 patients were analyzed. Dose-limiting toxicity (DLT) did not occur in the first 3 patients treated with irinotecan at 80 mg/m 2 (level 2), but developed in 3 of the 6 patients who received irinotecan at 90 mg/m 2 (level 3). Then DLT occurred in 3 other patients at level 2. At level 2 or 3, DLT comprised neutropenia, thrombocytopenia, and diarrhea. Level 2 was designated as the maximum tolerated dose, and level 1 as a recommended dose (RD). The pathological complete response rate was 28%, and the down-staging rate was 56%. Conclusions: Our results suggested that the RD of irinotecan when combined with preoperative S-1 and pelvic radiation was 60 mg/m 2 .